2018
DOI: 10.1016/j.tins.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Understanding and Treating SCN2A-Mediated Disorders

Abstract: Advances in gene discovery for neurodevelopmental disorders have identified SCN2A dysfunction as a leading cause of infantile seizures, autism spectrum disorder, and intellectual disability. SCN2A encodes the neuronal sodium channel Na1.2. Functional assays demonstrate strong correlation between genotype and phenotype. This insight can help guide therapeutic decisions and raises the possibility that ligands that selectively enhance or diminish channel function may improve symptoms. The well-defined function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
269
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 236 publications
(297 citation statements)
references
References 85 publications
12
269
0
3
Order By: Relevance
“…The PTVs in SCN2A/3A/8A do not lead to a clinically defined epilepsy syndrome but to heterogeneous NDDs, including autism with or without later onset seizures. 15,17,22,26,40 Moreover, in the SCN CNV cohort, we observed that patients with duplications presented with significantly earlier seizure onset and responded better to SCBs compared to patients with deletions. This early seizure onset is likely caused by duplication of the SCN2A/SCN3A genes, which are the earliest SCNs expressed during development, resulting in GoF effects due to SCN2A/SCN3A protein overexpression.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…The PTVs in SCN2A/3A/8A do not lead to a clinically defined epilepsy syndrome but to heterogeneous NDDs, including autism with or without later onset seizures. 15,17,22,26,40 Moreover, in the SCN CNV cohort, we observed that patients with duplications presented with significantly earlier seizure onset and responded better to SCBs compared to patients with deletions. This early seizure onset is likely caused by duplication of the SCN2A/SCN3A genes, which are the earliest SCNs expressed during development, resulting in GoF effects due to SCN2A/SCN3A protein overexpression.…”
Section: Discussionmentioning
confidence: 64%
“…By contrast, the majority of SCN2A/3A/8A ‐associated early onset epilepsies including benign epilepsies and epileptic encephalopathies are caused by GoF missense variants and full gene duplications. The PTVs in SCN2A/3A/8A do not lead to a clinically defined epilepsy syndrome but to heterogeneous NDDs, including autism with or without later onset seizures . Moreover, in the SCN CNV cohort, we observed that patients with duplications presented with significantly earlier seizure onset and responded better to SCBs compared to patients with deletions.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…34 This similarity may not be coincidental, as both channels are localized at the axon initial segment and seizures in early epilepsy caused by KCNQ3 LoF variants, like those caused by SCN2A GoF variants, are responsive to sodium channel blockers, such as carbamazepine. In particular, it is unclear why the LoF condition presents in the neonatal period, whereas the GoF condition results in cognitive and behavioral disturbances that only become apparent later.…”
Section: Kcnq3 and Kcnq2 Genotypes And Phenotypesmentioning
confidence: 99%